A framework for the timing of the final meltwater outbursts from glacial Lake Agassiz-Ojibway. (15th December 2021) - Brouard, Etienne; Roy, Martin; Godbout, Pierre-Marc; Veillette, Jean J.
Abstract: The climate variability of the last deglaciation is often linked to meltwater discharges from the melting of large ice sheets. One of the best examples comes from the drainage of glacial Lake Agassiz-Ojibway (LAO) and its attendant perturbation of the Atlantic Meridional Overturning Circulation (AMOC), which has long been held responsible for a rapid cooling at ∼8.2 ka. However, recent modeling studies have argued that a large and sustained freshwater flux linked to increased surface melt and ensuing collapse of the Laurentide Ice Sheet (LIS) dam may have formed an efficient forcing for this cooling event. Yet, empirical (geological) evidence for a long-lasting meltwater flux is still equivocal while paleoceanographic data show that the freshening of the North Atlantic around the 8.2-ka cold event is characterized by multiple freshwater pulses. Part of this uncertainty arises from the lack of constraints on the structure (number) and timing of meltwater discharges involved in the drainage of LAO, which prevents a detailed assessment of the freshwater forcing mechanisms at work and their potential impact on AMOC—an important issue given the present-day increase in the melting of the cryosphere around the North Atlantic. Here, we review 597 14 C ages from marine and continental sediment archives and use 296 of these 14 C ages along with LAO geomorphological and varve records to present an integrated framework constraining the timing of LAO meltwater outbursts across the final deglaciation interval. Results show that LAO drained through two distinct events: first subglacially at ∼8.22 cal ka BP and then after the breakup of the ice dam at ∼8.16 cal ka BP. These LAO meltwater discharges are coeval with two important freshwater pulses in North Atlantic sediment cores, with the largest meltwater outburst matching the onset of the 8.2 ka event in Greenland ice cores. These results suggest that, in a fast-changing ocean-climate system influenced by melting ice sheets like that of the late deglaciation, massive and short-lived freshwater injections can potentially have an impact on AMOC. Highlights: We review sediment archives linked to the drainage of Lake Agassiz-Ojibway (LAO). We use 296 14C ages (out of 597) to constrain the timing of LAO meltwater pulses. LAO drained through two closely-spaced discharges at ∼8.22 and ∼8.16 cal ka BP. LAO meltwater discharges are coeval with freshwater pulses in the Labrador Sea. Relatively small meltwater discharges may form an efficient freshwater forcing.